The biomechanics of standing start and initial acceleration: Reliability of the key determining kinematics - Standing, R. J.; Maulder, P. S. (Journal of Sports Science & Medicine, 2017)
The key determining kinematic variables associated with short sprint performance provide insight into how and why movement may vary between individual trials. Currently, literature surrounding these determinants is scarce when investigating the first three strides of a sprint. The purpose of this study was to investigate the reliability of sprint acceleration and the key kinematic determinants involved during the first three steps of the movement. The aim was to use a practical method of kinematic analysis to help explain why changes may occur in sprint performance via the use of correlative statistics and to provide reference values for intervention research to make conclusions about their change scores. Ten male volunteers from various team sports attended two separate testing sessions, a minimum of 48 hours apart. They performed three maximal sprint trials over a 10m distance from a standing start, where researchers captured 5m and 10m sprint times alongside high speed camera footage, from which the key kinematic variables were measured. Results demonstrated that although 5m and 10m sprint times depicted moderate to large levels of similarity between sessions, neither of these variables met the criteria to be classified as adequately, or highly reliable. Kinematic measures typically produced ICC values > 0.70 and CV% < 10%, demonstrating all relevant statistical traits to be categorised as reliable measures. Step frequency and flight time during the third step showed the largest correlation with performance, exhibiting `r` values of -0.386 and 0.396, respectively. These findings demonstrate that kinematic variables may not have an influential role with sprint times; therefore suggesting kinetic concepts may in fact be the key determinants of speed. Future research is required investigating the interaction of kinetic and kinematic variables associated with sprinting and how the variability in these concepts effects the reliability of performance.